Beyond the Middle East; Analyzing the Islam Nusantara Concept as a Global Model for Moderate and Contextual Islam - Md Shodiq; Nurul Huda; Haziq Idris (Yayasan Adra Karima Hubbi, 2025)
Global Islamic discourse is dominated by Middle Eastern centrism. Indonesia promotes Islam Nusantara (Archipelagic Islam), emphasizing moderation and syncretism (adat), aiming to be a global counter-model for reconciling faith, democracy, and modernity. This study aimed to analyze the strategic efficacy and global reception of Islam Nusantara among Middle Eastern religious elites and Western policymakers, addressing the critical Theological-Policy Translation Gap hindering its soft power projection. A qualitative, comparative multi-site case study (N=25 elite informants) was conducted, including Indonesian propagators, Salafi critics, and integration experts. Data were gathered via interviews and analyzed using a Policy Translation Matrix. The campaign is severely constrained by the Translation Gap. Middle Eastern elites rejected the concept based on Theological Purity (bid’ah). Western policymakers marginalized it due to a lack of Policy Utility and secular framing, proving the uniform message failed to satisfy opposing filters. The findings mandate an urgent dual-track communication strategy. The study’s contribution is a novel Global Policy Strategy for Contextual Islam that requires focusing on rigorous Arabic fiqh scholarship for the East and pragmatic, secular policy framing for the West.